Cultural learning styles in language education a special reference to Asian learning styles - Li, Lynne N. (New York, NY : Routledge, 2022)
This book presents a nuanced look at the relationship between language learning styles and culture to illuminate how these important constructs are understood, employed and play out in the real world. Through the lens of different learning style dimensions--cognitive, affective, process-centred, environment-centred and cultural--Li unpacks and examines the commonly accepted tensions between learning styles, culture, teacher assumptions and teaching approaches. With a focus on Asian learning styles and Chinese learners, Li addresses the past and current debates and reconceptualises the roles and tensions between students' learning, students' cultural backgrounds and teaching styles. Li adeptly navigates this controversial arena to demystify preconceptions and provide avenues for innovative and effective classroom practices in language teaching. Ideal for pre-service ESL/EFL teachers, researchers and scholars, this book bridges the gap between research and practice on culture and language learning in the classroom.
Keywords: English language -- Study and teaching -- East Asia; English language -- Study and teaching -- Chinese speakers; Second language acquisition; Language and culture -- East Asia; Cognitive styles -- East Asia; Learning -- East Asia; Learning, Psychology of; Teaching -- Methodology; EDUCATION / Multicultural Education